The impact thinking framework: a process for advancing research-to-practice initiatives in neuroaesthetics - Magsamen, Susan; Golden, Tasha L.; Towriss, Catriona A.; Allen, Joy (Frontiers in Psychology, 2023)
Neuroaesthetics research explores brain, body and behavioral responses to engagement with the arts and other aesthetic sensory experiences. Evidence indicates that such experiences can help address various psychological, neurological and physiological disorders, and that they can support mental and physical well-being and learning in the general population. The interdisciplinary nature of this work contributes to its impact and promise; however, it also creates challenges as various disciplines approach and define research and practice in varied ways. Recent field-wide reports have noted that a consensus translational framework is needed to support further neuroaesthetics research that can deliver meaningful knowledge and interventions. The Impact Thinking Framework (ITF) was designed to meet this need. Through a description of the framework’s nine iterative steps and a presentation of three case studies, this paper posits that the ITF can support researchers and practitioners in understanding and applying aesthetic experiences and the arts to advance health, well-being, and learning.